Enabling technologies for circular economy in the construction sector - Monica Lavagna; Serena Giorgi; Daniela Pimponi; Andrea Porcari (Techne)
Enabling Technologies have the potential to transform both the physical flow of materials and resources (production and construction methods), and the intangible organisational and managerial relationships (exchange and monitoring of data and relationships along the entire chain of value). They should, therefore, be considered important in supporting change processes aimed at the circular use of resources. This paper presents some research and experiments, at European and Italian level, aimed at developing and applying Enabling Technologies for circular economy, and at aligning them with the needs and challenges of society, by directly involving actors of the building sector ecosystem in moments of discussion and co-creation to define potential strategies and operational actions for innovation in the sector.